Effect of fertility levels and biofertilizers on the chemical and biological properties of soil under late sown chickpea [Cicer arietinum L.] - Gaurav Verma; Deen Dayal Yadav; Amit Kumar; Gaurendra Gupta; Vinod Kumar Sharma; Pravin Kumar Upadhyay; Satyaveer Singh (Annals of Agricultural Research, 2023)
A field experiment was conducted during Rabi season of 2016-2017 at the SIF Farm of CSAUAT, Kanpur, Uttar Pradesh to evaluate the fertility levels and biofertilizers on the chemical and biological properties of soil under late sown chickpea [Cicer arietinum L.]. The experiment comprised of 12 treatments combination and laid out in split plot design 4 RDFs control, RDF 100%, 75% RDF and 50% Recommended dose of fertilizer with assigned in main plot. Each main plot further divided into 3 sub plot accommodate three levels of biofertilizers Rhizobium + PSB, Rhizobium + PGPR and Rhizobium + PSB + PGPR and replicated thrice. The result showed that among the different fertility levels, application of 100% RDF were recorded significantly better chemical properties, microbial populations and enzymatic activity after harvest of chick pea crop. Among the biofertilizer treatments, application of Rhizobium + PSB + PGPR were resulted significantly better chemical properties, microbial populations and enzymatic activity followed by 75% RDF after harvest of chick pea crop under late sown condition.